In Situ Tin(II) Complex Antisolvent Process Featuring Simultaneous Quasi‐Core–Shell Structure and Heterojunction for Improving Efficiency and Stability of Low‐Bandgap Perovskite Solar Cells. Issue 8 (17th January 2020) - Li, Can; Ma, Ruiman; He, Xinjun; Yang, Tingbin; Zhou, Ziming; Yang, Shuo; Liang, Yongye; Sun, Xiao Wei; Wang, Jiannong; Yan, Yanfa; Choy, Wallace C. H.
Abstract: Unlike Pb‐based perovskites, it is still a challenge for realizing the targets of high performance and stability in mixed Pb–Sn perovskite solar cells owing to grain boundary traps and chemical changes in the perovskites. In this work, proposed is the approach of in‐situ tin(II) inorganic complex antisolvent process for specifically tuning the perovskite nucleation and crystal growth process. Interestingly, uniquely formed is the quasi‐core–shell structure of Pb–Sn perovskite–tin(II) complex as well as heterojunction perovskite structure at the same time for achieving the targets. The core–shell structure of Pb–Sn perovskite crystals covered by a tin(II) complex at the grain boundaries effectively passivates the trap states and suppresses the nonradiative recombination, leading to longer carrier lifetime. Equally important, the perovskite heterostructure is intentionally formed at the perovskite top region for enhancing the carrier extraction. As a result, the mixed Pb–Sn low‐bandgap perovskite device achieves a high power conversion efficiency up to 19.03% with fill factor over 0.8, which is among the highest fill factor in high‐performance Pb–Sn perovskite solar cells. Remarkably, the device fail time under continuous light illumination is extended by over 18.5‐folds from 30 to 560 h, benefitting from the protection of the quasi‐core–shell structure. Abstract : A novel in‐situ tin(II) complex antisolvent process is employed to simultaneously form quasi‐core–shell structure and heterojunction in mixed Pb–Sn low‐bandgap perovskite solar cells. This quasi‐core–shell structure offers effective grain boundary trap passivation and the heterostructure significantly improves the carrier extraction, leading to highly improved electrical property and stability.